(untitled) (ModaPalavra e-periódico, 2016)
The purpose of this article is to bring techniques for patterns setting from geometric shapes, such as quads, triangles and hexagons, along with symmetry. Seeking references in the Surface Design Fundamentals presented by Rüthschiling (2008) thus seeks to bring basic concepts to understand the setup process surface design going through the steps: Choose theme [theme]; Development of elements / reasons; Choice of colors; Construction of the module; Repeat [Generation alternatives]. It is worth mentioning, this article intends to work with the concept of Rapport is a model used to set different standards based on the same module, changing, for example, the direction or rotation of their cash -usuallyin this model the module base figure is the square or rectangle. However, this article seeks to demonstrate how to use other geometric shapes [as hexagons and triangles].